(untitled) (African Journal of Biomedical Research, 2021)
The present policy in South Africa is for healthcare users to report adverse drug reactions through medical practitioners, pharmacists, nurses, dentists, or veterinarians. This study aimed to develop a web-based application as an interventional tool for reporting adverse drug reactions. The software will also serve as an educational program to create awareness and encourage reporting by healthcare users directly to the pharmacovigilance authority. Previous studies were carried out by reviewing directs reporting in Africa to survey the view of healthcare users on direct reporting in South Africa and methods of direct reporting. Findings from these studies resulted in the development of a user-centred web application. Heuristic evaluation (n=3) and small-scale usability testing was carried out. The objective (task success rate) and subjective (system usability scores) metrics were used to test the usability of the application among participants (n=22). This was followed by redesigning the application before the final presentation. Results: An easily accessible digitalised adverse drug reporting web-based application named SA-VigiApp® was developed. It has health information tips as an educational intervention. The initial heuristics evaluation affirmed that the web application has Six (6) out of the 10 items on Nielsen’s Heuristic checklist. A total of 22 participants aged 18 and above were recruited for small-scale usability testing. Majority of the participants (n= 11; 50%) accessed the web application with the use of android mobile phones while others used computer laptops (n=6; 27.3%), iPhones (n= 4; 18.2%) and tablet (n=1; 4.5%). The mean task success rate was 84.2% with 7 out of 11 tasks completed successfully. The usability score was 76.7%. The application was redesigned following the responses and comments from the usability testing. Results suggest that participants rated this application as usable. The redesigned application has all the main features for adverse drug reaction reporting and user’s acceptability that will be useful for a prompt rate of report submission. It will also serve to create awareness and inform users on medication-related issues.